Desain dan Implementasi Sistem Pakar Diagnosa Penyakit Menggunakan Forward Chaining - Saputri, Vettyca Diana (CV. Generasi Insan Rafflesia, 2024)
The development of information technology has encouraged the utilisation of expert systems in various fields, including health. An expert system is a computer system designed to mimic the ability of an expert to make decisions. This article discusses the design and implementation of an expert system to diagnose diseases based on the forward chaining method. This method works by tracing the facts provided by the user to the right conclusion. The purpose of this research is to assist the community in making an initial diagnosis of common diseases. The implementation results show that the system is able to provide accurate diagnosis results based on the symptoms entered by the user.